The Influence of Leadership Style on Employee Performance and Motivation at Aqua Home Service Mulia Bogor Regency - Mulyana; Muliadi, Dedi (Journal Business Inovation, Accounting and Management, 2025)
This study aims to analyze the influence of leadership style on employee performance and motivation at Aqua Home Service Mulia, Bogor Regency. The research method used was a quantitative method with data collection through a questionnaire filled out by 30 respondents, namely Aqua Home Service Mulia employees. The variables measured in this study include leadership style as an independent variable, as well as employee performance and motivation as a bound variable. The results of the study show that leadership style has a significant positive influence on employee performance and motivation. In particular, the leadership style applied by managers and team leaders is proven to improve employee performance and arouse their work motivation. The influence of leadership style on motivation also showed significant results, indicating that good leadership can strengthen employees' commitment and enthusiasm at work. In addition, employee motivation was also found to have a positive influence on their performance, which means that motivated employees have better performance. These findings show that companies need to pay attention to the implementation of effective leadership styles to improve employee motivation and performance, which can ultimately improve the overall productivity of the organization. This research is expected to contribute to the development of leadership strategies in companies.